Incremental Innovation and Progress in Advanced Squamous Cell Lung Cancer: Current Status and Future Impact of Treatment. Issue 12 (December 2016) - Langer, Corey J.; Obasaju, Coleman; Bunn, Paul; Bonomi, Philip; Gandara, David; Hirsch, Fred R.; Kim, Edward S.; Natale, Ronald B.; Novello, Silvia; Paz‐Ares, Luis; Pérol, Maurice; Reck, Martin; et al.
Abstract : ABSTRACT : Squamous cell lung cancer (sqCLC) is an aggressive form of cancer that poses many therapeutic challenges. Patients tend to be older, present at a later stage, and have a high incidence of comorbidities, which can compromise treatment delivery and exacerbate toxicity. In addition, certain agents routinely available for nonsquamous cell histologic subtypes, such as bevacizumab and pemetrexed, are contraindicated or lack efficacy in sqCLC. Therapeutic progress has been much slower for advanced sqCLC, with median survival times of approximately 9 to 11 months in most studies. Herein, we discuss the current therapeutic landscape for patients with sqCLC versus with nonsquamous NSCLC. Current evidence indicates that new targeted treatments, notably monoclonal antibodies such as ramucirumab and necitumumab, and immunotherapies such as nivolumab and pembrolizumab can provide survival prolongation, although the benefits are still relatively modest. These incremental improvements, all realized since 2012, in aggregate, will very likely have a clinically meaningful impact for patients with sqCLC. We also discuss recent genomic studies of sqCLC that have identified potentially actionable molecular targets, as well as the relevant targeted agents in clinical development. Finally, we discuss the magnitude of survival benefit and the risk‐to‐benefit ratio that would prove clinically meaningful in this underserved patient population with unmet needs.